Modeling and thermodynamic analysis of thermal performance in self-pressurized liquid hydrogen tanks. (19th August 2022) - Wang, H.R.; Wang, B.; Pan, Q.W.; Wu, Y.Z.; Jiang, L.; Wang, Z.H.; Gan, Z.H.
Abstract: Liquid hydrogen (LH2 ) is one of the most economic methods for large-scaled utilization of hydrogen energy. However, safe operation and storage of LH2 relies on accurate prediction of the pressure rise and adequate investigation on thermal behaviors inside LH2 tank. In light of this, a modified thermal multi-zone model (TMZM) considering heat and mass transfer between vapor and liquid is developed in this paper. The model has a maximum relative error of 4.67% in predicting pressure rise against the experimental results from NASA. A thermodynamic analysis method is proposed to clarify the influences of key parameters including the temperature, compressibility factor and density of vapor, and working conditions including heat leakage and initial superheated degree on the pressurization rate. The results indicate that temperature of vapor in the ullage and vapor-liquid interfacial mass transfer rate are two main parameters determining the pressurization rate, and the effects of the two parameters are different between different stages. The distinction of stages depends on heat leakage and initial superheated degree. For the working condition with an initial filling rate of 50% and a heat leakage of 10 W, temperature of vapor is the parameter dominates pressurization rate during 96.8% of the whole self-pressurization process. Heat leakage also has a vital impact on the distinction of stages, when heat leakage increases to 80 W, the temperature of vapor dominating stage will reduce to 46.4%. Furthermore, pressurization rate is sensitive to initial superheated degree in the ullage. An increase of 4 K of the initial superheated degree leads to a 53.3% decrease of the pressurization rate. This study provides a useful method for the reliable design and quick optimization of high performance LH2 tanks. Graphical abstract: Image 1 Highlights: A modified model developed to predict pressure build-up for LH2 tanks. Investigation of thermal behaviors in LH2 tanks. Thermodynamic analysis on pressurization rate. Impacts of heat leakage and initial superheated degree are discussed. Strategies of extending the holding time are proposed.